2002
DOI: 10.2135/cropsci2002.2031
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Membrane Polar Lipid Fatty Acids of Seashore Paspalum in Response to Low Temperature Exposure

Abstract: ters, however, these organs can be killed when the frost zone moves below the rhizome layer. Even during rela-Seashore paspalum (Paspalum vaginatum Sw.) is a warm-season tively mild winters, the crowns and rhizomes are suscepturfgrass, best known for its superior salt tolerance. Plants are subject tible to injury due to the cold. Reestablishment of damto injury during winter conditions along the northern boundary of aged turf is expensive both in terms of labor and plant their zone of adaptation. New cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 24 publications
4
87
1
Order By: Relevance
“…One of the most notable differences between our data and that from previous studies is that we observed a negative correlation between fat content and overwintering ability. This finding is in contrast to observations on Arabidopsis above-ground growth [37] and what was hypothesized for the genus Paspalum based in part on studying rhizomes cut from plants and buried in the ground [38,39]. Although our finding was unexpected, it is supported by significant correlations during both sampling dates for the College Station soil column studies.…”
Section: Assimilate Concentrations and Overwinteringcontrasting
confidence: 99%
See 1 more Smart Citation
“…One of the most notable differences between our data and that from previous studies is that we observed a negative correlation between fat content and overwintering ability. This finding is in contrast to observations on Arabidopsis above-ground growth [37] and what was hypothesized for the genus Paspalum based in part on studying rhizomes cut from plants and buried in the ground [38,39]. Although our finding was unexpected, it is supported by significant correlations during both sampling dates for the College Station soil column studies.…”
Section: Assimilate Concentrations and Overwinteringcontrasting
confidence: 99%
“…In fact, if higher fat content allows a plant to continue to metabolize at lower temperatures, it may also cause the plant to use its stored energy during the winter months and deplete the plant of resources for regrowth the following year, therefore decreasing the rhizomes' ability to successfully overwinter. Another possible explanation for our findings is that the ratio of different fatty acids may be more influential to cold tolerance than the total fat content [38,40]. Similar to fat, starch concentrations were negatively correlated with overwintering.…”
Section: Assimilate Concentrations and Overwinteringmentioning
confidence: 79%
“…This is accompanied by changes in lipid composition that modulate membrane stabilization (Thomashow, 1999). Increases in the proportion of PL in the plasma membrane during cold acclimation are commonly observed in various herbaceous and woody species, such as rye (Uemura and Steponkus, 1994), oat (Avena sativa; Uemura and Steponkus, 1994), seashore paspalum (Paspalum vaginatum; Cyril et al, 2002), Arabidopsis (Uemura et al, 1995;Welti et al, 2002), and mulberry (Morus bombycis; Yoshida, 1984). Under low-temperature stress, an increase in the ratio of unsaturated PL is a crucial factor in maintaining the biological functions of membranes (Nishida and Murata, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Responses of plants to hardening were observed on oligogenic traits such as (1) accumulation of sucrose and other simple sugars (Pollock 1986;Santoiani et al 1993), (2) increase of total protein concentration (Davis and Gilbert 1970;McKenzie et al 1988), (3) accumulation of free proline (Petcu and Terbea 1995;Dörffling et al 1997;Thomashow 1999), (4) increase of the cell membranes stability (Chandrasekar et al 2000), (5) increase of total lipids and their polyunsaturated fatty acid content (linoleic and linolenic acids), and (6) increase of desaturase enzyme activity (Cyril et al 2002;Wei et al 2005). Recent studies in faba bean showed that polyunsaturated fatty acid accumulation were adaptation mechanisms to low non-freezing temperatures, but also significant correlated traits to frost tolerance (Arbaoui et al 2008).…”
Section: Introductionmentioning
confidence: 99%